Out of “Borrowed Space”: Multi-Culturalist Discourse and Historiography in the Twenty-First Century - Nilgün Anadolu-Okur (İnsan & Toplum)
Built upon contemporary discourses about centeredness and multi-culturalist ap- proaches to history and the making of historiography, this study aims to explore the beginnings of the Afrocentric movement in the 1980s as a leading argument against the advent of Eurocen- trism, and Eurocentric interpretations of historiography, civilizational agency and organization within academia in the United States. Black Power and Black Arts Movements have contributed to the formation of Black Studies programs and departments throughout the U.S. facilitating the spread of Afrocentric thought. In its demystification of Western etymology and Eurocentric argu- ments on universality, and historical precedence, Afrocentricity has played a fundamental role in steering culture-centered ideologies to a multitude in the Middle East, North Africa, Asia and the Far East which were particularly polarized after September 11, 2001. It has also been influential in generating conflict-resolution discourses while expanding culturalist positions in defense of civil liberties throughout the world.